Assessing learning about food safety using Personal Meaning Maps - Silva, A.; Junqueira, L.; Truninger, M.; Delicado, A.; Csenki, E.; Fehér, Á.; Ózsvári, L.; Szakos, D. (Health Education Journal, 2023)
Objective: According to the World Health Organisation’s estimates, food contamination is linked to 23 million cases of illness and 5,000 deaths per year in Europe. While changes in food production and distribution play an important role in managing contamination risk, foodborne illnesses can originate in food-handling practices at home. This study aimed to assess how a food safety education initiative in which students learned about food safety risks and minimising risk behaviour improved students’ knowledge about food safety. Setting: Three public schools, two in Hungary and one in Portugal. Methods: A study of 105 Hungarian and Portuguese students between 11 and 18 years of age were invited to prepare Personal Meaning Maps before and after the delivery of a food safety lesson delivered by a school science teacher. Knowledge and risk perceptions of food safety, before and after the delivery of the lesson, were assessed both quantitatively and qualitatively. Results: Food safety topics that were scored highest were those that already had strong scores in the diagnostic phase, such as those related to personal hygiene and use-by dates. However, the largest increases in mastery scores were in less-known-about topics such as cold chain and cross-contamination risks. Idea associations take place often by linking specific contents to already-known-about concepts. Conclusion: Findings show that students more readily engaged with practical concepts directly linked to their experience of food handling at home than to more abstract concepts of food safety and contamination.